Recurrent child mortality risks and parity transition in Nigeria - Abiodun Idowu Adanikin; Sabu S. Padmadas; Nuala McGrath (BMC, 2019)
Abstract Background Fertility rates remain persistently high in Nigeria, with little difference across socioeconomic groups. While the desire for large family size is culturally rooted, there is little understanding of how repeated child mortality experiences influence fertility behaviour and parity transition in Nigeria. Methods Using birth history data from the 2013 Nigeria Demographic and Health Survey (NDHS), we applied life table techniques and proportional-hazard regression model to explore the effect of child survival experience on parity transitions. We hypothesize that a woman with one or more child death experience is at elevated risk of progressing towards higher parities. Results Our findings show that child mortality is concentrated among mothers living in deprived conditions especially in rural areas of the northern part of Nigeria and among those with little or no education and, among those belonging to Hausa/Fulani ethnicity and Islam religion. Mothers with repeated experience of child deaths were significantly at a higher rate of progressing to higher parities than their counterparts (HR: 1.45; 95% CI: 1.31-1.61), when adjusted for relevant biological and socio-demographic characteristics. Conclusion Recurrent experience of child deaths exacerbates the risks to higher parity transition. Interventions aimed at reducing fertility in Nigeria should target promoting child survival and family planning concurrently.